Tuning the optical and electrochemical properties of conjugated all-thiophene dendrimers via core functionalization with a benzothiadiazole unit. Issue 3 (5th January 2017) - Gao, Wei; Wang, Junkai; Luo, Qun; Lin, Yi; Ma, Yuchao; Dou, Junyan; Tan, Hongwei; Ma, Chang-Qi; Cui, Zheng
Abstract : The optoelectronic properties of conjugated thiophene dendrimers can be tuned by core functionalization with a benzothiadiazole unit. Abstract : Three-dimensional (3D) π-conjugated dendrimers are a new class of structurally defined macromolecules for use in organic electronics. Herein, a new family of dendritic oligothiophenes (DOT-c-BTs) up to the 2 nd generation with benzothiadiazole (BT) groups at the core have been synthesized by a precise convergent approach. The well-defined chemical structures and the monodispersed nature of these DOT-c-BTs were fully confirmed by NMR spectroscopy, MALDI-TOF mass spectrometry (MALDI-TOF MS), high-resolution mass spectrometry (HR MS), and gel-permeation chromatography (GPC) measurements. The optical and electrochemical properties were investigated by UV-vis absorption, and cyclic voltammetry. The insertion of electron-deficient benzothiadiazole (BT) groups into the core of the conjugated dendritic oligothiophenes resulted in a large redshift compared to all -thiophene dendrimers. Cyclic voltammetry measurements showed one reversible reduction process and multiple oxidation waves for these functionalized dendritic oligothiophenes, due to the reduction of the BT core and the oxidation of different π-conjugated chains, respectively. Applications of DOT-c-BTs in organic solar cells as the electron donor were presented. However, unfavorable nanophase separation in the blended film led to poor device performance.